2008
DOI: 10.1590/s1516-31802008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal lymphadenectomy for treating metastatic melanoma: case report

Abstract: CONTEXT: Regional lymph node involvement in patients with malignant melanomas has been associated with poor prognosis. In-transit metastases also lead to poor long-term survival. Whereas for nodal disease only regional lymphadenectomy offers adequate locoregional control, for in-transit metastasis both local excision and isolated limb perfusion with chemotherapy plus tumor necrosis factor-alpha can be used for disease control. In cases of tumors located in the distal region of the legs, the lymphatic dissemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Although rare as an operation, popliteal lymphadenectomy is the treatment of choice in cases of localized clinical or microscopic disease [13][14][15]. Prophylactic dissection of the popliteal nodes is not considered necessary [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare as an operation, popliteal lymphadenectomy is the treatment of choice in cases of localized clinical or microscopic disease [13][14][15]. Prophylactic dissection of the popliteal nodes is not considered necessary [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Popliteal lymphatic metastases from melanomas located in the distal region of the lower extremities (lower legs or feet) are extremely rare; there are few reports on such metastases in the literature because of the difficulty in examining the popliteal fossa, where the nodes lie deep in the fascia and are not easily palpable. 1,2 This initial obstacle tends to lead to a delayed diagnosis; therefore, the disease may only be discovered at a late stage. 2 Simultaneous popliteal and inguinal lymph node metastases are also quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This initial obstacle tends to lead to a delayed diagnosis; therefore, the disease may only be discovered at a late stage. 2 Simultaneous popliteal and inguinal lymph node metastases are also quite rare. Kretschmer et al 4 reported that among 166 patients with distal melanomas, only 16 (9.6%) showed popliteal sentinel lymph node (SLN) involvement on lymphoscin-tigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations